Esteriótipos e construção de identidade: uma análise discursiva sobre mitos de escolha de carreira profissional - Machado, Fabiani Debortoli Pereira (2016)
This study is characterized as a bibliographic research with a qualitative approach, it thematizes about myths of career choice, prioritizing, on a discursive analysis, issues related to cultural stereotypes and identity construction. The corpus consists of three news collected from three websites – G1, Infomoney and Exame. The selection criteria was the presence of the word "myth" associated in the title of the news to the sentence "career choice" or "professional vocation". From this corpora it was outlined as the general objective of this research to analyze how the discursive ethos, shown in the identity construction of myths about career choice, can represent change or maintenance of cultural references in the choice of profession by the young student. To support the analysis developed, which aims to encompass an interface between discourse analysis and studies on culture and identity, the contributions of the following authors were mobilized: Geertz (1926/2011), De Certeau (1995) and Cevasco (2008), about cultural studies, Bourdieu (1989/1998) and his contributions about the simbolic power and Hall (2003, 2004, 2006), Bauman (2009) and Castells (1999) on the identity field. In regard to speech analysis, we used the global semantic theory particularizing the theoretical cathegories of scenography and ethos, based on Maingueneau (1984/2008a, 2008b, 2010, 2015) and Amossy (2014). It appears, based on the analysis performed, the scenography of the myths is built from validated scenes, which inevitably betray a symbolic power. Still, the cultural identity, in a way, provides base for the spread or extinction of the myths.